2015
DOI: 10.2147/ijn.s95440
|View full text |Cite
|
Sign up to set email alerts
|

Improving cytotoxicity against cancer cells by chemo-photodynamic combined modalities using silver-graphene quantum dots nanocomposites

Abstract: The combination of chemotherapy and photodynamic therapy has emerged as a promising strategy for cancer therapy due to its synergistic effects. In this work, PEGylated silver nanoparticles decorated with graphene quantum dots (Ag-GQDs) were tested as a platform to deliver a chemotherapy drug and a photosensitizer, simultaneously, in chemo-photodynamic therapy against HeLa and DU145 cancer cells in vitro. Ag-GQDs have displayed high efficiency in delivering doxorubicin as a model chemotherapy drug to both cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 51 publications
2
38
0
Order By: Relevance
“…47 Similarly, PEGylated silver nanoparticles coated with GQDs exerted a distinct antitumor effect at the level of 100 μg/mL by triggering apoptosis only in cancer cells without impacting the viability of normal cells. 48 Consequently, understanding of how to improve the antitumor effects and decrease the toxicity of normal cells may allow good use of GBMs in biomedicine.…”
Section: Gbms Induce Apoptosis In Cellsmentioning
confidence: 99%
“…47 Similarly, PEGylated silver nanoparticles coated with GQDs exerted a distinct antitumor effect at the level of 100 μg/mL by triggering apoptosis only in cancer cells without impacting the viability of normal cells. 48 Consequently, understanding of how to improve the antitumor effects and decrease the toxicity of normal cells may allow good use of GBMs in biomedicine.…”
Section: Gbms Induce Apoptosis In Cellsmentioning
confidence: 99%
“…Coupling graphene quantum dots with a photosensitizer can increase singlet oxygen generation above the amount produced by either compound alone and promote cellular toxicity (9)(10)(11)(12). The photosensitizer, methylene blue (MB), exhibits limited ability to permeate cell membranes, but can enter some cancer cells, and upon exposure to light cause significant production of singlet oxygen and other reactive oxygen species (ROS) that kill the malignant cells (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Habiba et al reported the synthesis of Ag-GQDs nanocomposite using pulsed laser and demonstrated good biocompatibility and non-toxicity of the nanocomposite. 16 Nonetheless, the effect of metallic atoms doping on the optical properties of GQDs has not been well-addressed. Non-metallic atoms doping has shown to vary the electronic structure of the GQDs, it is therefore of central importance to investigate the a E-mail: lxmscience@163.com b E-mail: scitang@163.com 2158-3226/2016/6(7)/075116/8 6, 075116-1 © Author(s) 2016.…”
Section: Introductionmentioning
confidence: 99%